Experimental study of micro-cracks in laboratory and in situ using infrared thermography - Eva Barreira (2014)
Non-destructive techniques are essential to detect common pathologies and analyse the building behaviour. Infrared thermography is a testing technology that has been applied to buildings diagnosis for some decades. However, there are still some applications which are not yet completely explored like the detection of micro-cracks on faÃ_ade coating materials. In this paper we present a brief introduction of the fundamentals of infrared thermography as well as the results of wetting and drying processes of wall coating samples with micro-cracks carried out in laboratory with very closely controlled climatic conditions. The results of an in situ campaign to evaluate this pathology in two distinguished faÃ_ades are also presented. This study reflects on the limitations of the application of infrared thermography to access micro-cracks and clearly demonstrates the difficulty on controlling measurements in field conditions due to the wide range of parameters that may affect the thermograms. Â(c) (2014) Trans Tech Publications, Switzerland.